The Impact of Clean and Healthy Living Behavior Program on the Independence and Discipline of Children Aged 4-5 Years - Rizka Maulida Mustika; Rina Wulandari (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
Clean and Healthy Living Behavior (CHLB) in early childhood is crucial for supporting children’s health, independence, and discipline. This study aimed to examine the effectiveness of the CHLB program on the independence and discipline of children aged 4–5 years. A quantitative ex post facto design was employed with a sample of 150 children from kindergartens in Banda Sakti District, selected through purposive sampling. The instruments were validated through content validity with reliability coefficients of 0.892 for independence and 0.948 for discipline. Data were analyzed using an independent sample t-test. The findings revealed significant differences in independence (Sig. 0.000 < 0.05; t = 5.832 > t-table 1.646) and discipline (Sig. 0.000 < 0.05; t = 8.591 > t-table 1.646) between schools that implemented CHLB for 10 years and 5 years. These results imply that CHLB programs can strengthen independence and discipline, and serve as a foundation for policy and early childhood education practices.